2016
DOI: 10.1002/macp.201500493
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-Based Gels

Abstract: Cellulose is the most available biomacromolecule in nature with the properties of renewability, biodegradability, biocompatibility, and environmental friendliness. Cellulose and its derivatives are excellent building blocks for fabrication of gels. In this review, the principles for preparing cellulose‐based gels are summarized in detail. Considering the native properties of cellulose and its derivatives, chemical and/or physical crosslinking can be introduced during the preparation of cellulose‐based gels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 180 publications
(205 reference statements)
0
35
0
Order By: Relevance
“…In bioprinting this often involves either a gelation process of a solution or, more commonly, thixotropic of a gel [13]. Cellulose is the most abundant biopolymer in the world and has been demonstrated to be a suitable polymer for applications in, for example, tissue engineering, filtration or separation [14]. However, cellulose in its native form is not water soluble and thus has proven challenging to process on bioprinters, either requiring the use of nanocellulose to form thixotropic and thus extrudable gels or suitable solvents to create cellulose solutions within a viscosity range that allows extrusion [15].…”
Section: Introductionmentioning
confidence: 99%
“…In bioprinting this often involves either a gelation process of a solution or, more commonly, thixotropic of a gel [13]. Cellulose is the most abundant biopolymer in the world and has been demonstrated to be a suitable polymer for applications in, for example, tissue engineering, filtration or separation [14]. However, cellulose in its native form is not water soluble and thus has proven challenging to process on bioprinters, either requiring the use of nanocellulose to form thixotropic and thus extrudable gels or suitable solvents to create cellulose solutions within a viscosity range that allows extrusion [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the abundant carboxymethyl groups make them very hydrophilic and thus limit their practical applications in aqueous environments. Covalent and non-covalent crosslinking methods are thus proposed to enhance the structure stability of the CMC-based materials [ 24 , 25 ]. Recently, the combination of poly (methyl vinyl ether-alt-maleic acid) (PMVEMA) and polyethylene glycol (PEG) with cellulosic materials has attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[9][10][11][12] Cellulose, which can be sustainably sourced and is biodegradable, has been evaluated as an alternative adsorbent for water purification. [13][14][15][16][17] For example, Tam and coworkers reported that hydrogel beads made from sulfated cellulose nanocrystals (S-CNCs) and alginate could efficiently remove 97% of methylene blue (MB) from aqueous solutions. [18] In a different example, Yu and coworkers showed that carboxylated cellulose nanofiber (CNF) aerogels removed MB with up to 95% efficiency.…”
Section: Introductionmentioning
confidence: 99%